1963
DOI: 10.1152/jappl.1963.18.6.1111
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of radius to pressure along the aorta in living dogs

Abstract: The instantaneous pressure-radius relationship and mean dimensions were studied at various sites along the aorta in 30 dogs. The pressure-radius relationship was studied in the living state using an electrical caliper to measure the radius continuously through the cardiac cycle. The relative dimensions of the aortic tree at branching sites were calculated from Jeltrate casts made immediately post mortem. The results indicate: 1) The value of ΔR/ΔP and the mean radius decreased with distance along the aorta. 2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
2
3

Year Published

1970
1970
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 144 publications
(53 citation statements)
references
References 0 publications
3
45
2
3
Order By: Relevance
“…As expected, AR direct and RP derived increased more gradually in comparison with aortic BP in this study. Although others have suggested that a strict linear relationship exists between aortic BP and dimensions, 21 our findings lend credence to more recent literature that describes a hysteretic (loop) relationship between aortic BP and dimensions. [22][23][24] Physiologically, this makes sense because there must be a delay in the volumetric increase (relative to pressure), while the aorta fills with blood ( Figure 4D-4I).…”
Section: Aortic Reservoir and Excess Pressure: A Physiological Paradigmsupporting
confidence: 88%
“…As expected, AR direct and RP derived increased more gradually in comparison with aortic BP in this study. Although others have suggested that a strict linear relationship exists between aortic BP and dimensions, 21 our findings lend credence to more recent literature that describes a hysteretic (loop) relationship between aortic BP and dimensions. [22][23][24] Physiologically, this makes sense because there must be a delay in the volumetric increase (relative to pressure), while the aorta fills with blood ( Figure 4D-4I).…”
Section: Aortic Reservoir and Excess Pressure: A Physiological Paradigmsupporting
confidence: 88%
“…The wide variation noted in the values of compliance listed in Table 1 are somewhat surprising, but are similar to the range of values obtained in studying the in vivo dynamic vessel mechanics in other arteries (7). At least a part of the differences may be explained by variations in vessel tone at the time of study, but it is our belief that these findings are indicative of a wide range of coronary artery compliance which is present in vivo.…”
Section: Discussionsupporting
confidence: 75%
“…Many studies using dogs have demonstrated that arterial pressure waveforms and diameter-change waveforms are similar [1,30]. We reported the similarity between carotid arterial pressure waveforms measured with a catheter-tipped micromanometer and carotid arterial diameter-change waveforms measured by echo tracking in humans [34].…”
Section: Measurements Of Pressure Waveformsmentioning
confidence: 58%